Pottery in Perspective: Life Cycle Thinking and Environmental Priorities in Craft Practice - Salani, Giorgio (European Journal of Sustainable Development, 2025)
A comparative Life Cycle Thinking (LCT) approach is used to assess the environmental significance of pottery-making within the broader context of everyday lifestyles. While craft ceramics are often seen as local, small-scale, and sustainable, they are also energy- and material-intensive. Drawing on a literature review of LCA studies of ceramic manufacturing, lifestyles and products - and informed by the author’s Life Cycle Analysis (LCA) of handmade pottery and ethnographic research in UK workshops - the study discusses Greenhouse Gas emissions (GHG) and other environmental impacts of craft ceramics. Although many practitioners are already improving efficiency in their studios, this paper argues that placing pottery within a wider lifestyle context reveals overlooked opportunities. The findings compare the impacts of pottery-making with aspects of daily life such as transport and dietary habits, offering a more proportionate view of environmental responsibility. The paper discusses priority interventions for the craft, supporting its role in the broader transition to more sustainable and decarbonized ways of living. Keywords: Life Cycle Thinking, craft ceramics, studio pottery, Life Cycle Analysis, carbon footprint